2017
DOI: 10.17559/tv-20161018122324
|View full text |Cite
|
Sign up to set email alerts
|

Regenerating the NC code in order to improve the surface quality

Abstract: Original scientific paper The paper presents the research results of the impact of variable machining parameters: feed and spindle speed on surface roughness of Aluminium alloy 6005-T6, at CNC in the up and down milling with tools of different dimensions and different materials (6 HSS, 6 VHM and 10 VHM). The properties and classification of Aluminium alloys are cited. The definition of surface roughness at end milling is given and parameters that affect it are specified. It was concluded that the feed is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…As the output characteristics of the process, the cutting force and the roughness of the treated surface were selected, as the most commonly used machinability [1,6]. Measurement of the cutting force was carried out using the measuring system shown in Fig.…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation
“…As the output characteristics of the process, the cutting force and the roughness of the treated surface were selected, as the most commonly used machinability [1,6]. Measurement of the cutting force was carried out using the measuring system shown in Fig.…”
Section: Experimental Partmentioning
confidence: 99%
“…Research in this paper was carried out on aluminum alloy 6061. Consequently, it can be concluded that this area is still interesting for research, that is, the optimization of parameters on new alloys has not been sufficiently investigated [6,7]. Another work, which certainly deserves readers' attention, is the work [8] where authors adapt parameter optimization in the milling process of AISI 1045 materials.…”
Section: Introductionmentioning
confidence: 99%